Correction of a deletion mutant by gene targeting with an adenovirus vector. - Wang, Q (1993)
The usefulness of adenovirus type 5 as a vector for homologous recombination was examined in CHO cells by using the adenine phosphoribosyltransferase (aprt) gene. Infection of a hemizygous CHO APRT- cell line containing a 3-bp deletion in exon 5 of the aprt gene with a recombinant adenovirus containing the wild-type gene resulted in restoration of the APRT+ phenotype at a frequency of 10(-5) to 10(-6) per infected cell. A relatively high frequency (approximately 6 to 20%) of the transductants appears to result from a homologous recombination event. The mutation on the chromosomal aprt gene is corrected in the homologous recombinants, and APRT expression is restored to a normal hemizygous level. Neither adenovirus nor exogenous promoter sequences are detected in the homologous recombinants. The remaining transductants result from random integration of the aprt gene with the adenovirus sequence. A number of adenovirus vectors containing different promoter sequences linked to the hamster aprt gene were constructed. A possible role for the promoter region in the homologous recombination event was indicated by the lack of homologous recombination in constructs lacking an active promoter.